Solid state switching control methods: A bibliometric analysis for future directions - Arsad A.Z.; Sebastian G.; Hannan M.A.; Ker P.J.; Rahman M.S.A.; Mansor M.; Lipu M.S.H. (MDPI AG, 2023)
Recently, the development and controls of solid-state switching have gained significant popularity over the years especially in academic research. The development of control strategies in solid state switching applications to ensure fast switching in a protected distribution system has fueled a great deal of investigation and further developments. Therefore, a critical review and analysis in the field of solid-state switching for distribution systems are provided in this article. The Scopus database is used to compile a list of the most cited published papers in the field of solid-state switching control methods based on the identified criteria. The study explores 120 of the most cited articles emphasizing six keywords such as a solid-state breaker, solid-state transfer switch, static transfer switch, automatic transfer switch, automatic protection switches, and solid-state protection switch. The analysis was conducted using the Scopus database in the fourth week of January 2021. The 120 articles were collected from 24 different journals and 27 different countries. It is reported that 78% of the published papers outline the methodology based on control and test systems whereas 22% of articles are based on review surveys. From that, 73% of articles concentrate on the protection strategy in the system. The main objective of the article is to classify and define the highly cited published articles in the field of solid-state switching control methods as well as to provide direction for future research on fast switching in the distribution system. The analysis also highlights various factors, issues, challenges, and difficulties to identify the existing limitations and research gaps. This review will serve to strengthen the development concepts of solid-state switching control methods towards achieving improved operational performance, energy-saving, economic prosperity, and enhanced power quality. The authors believe that this bibliometric evaluation will allow academic researchers to identify opportunities for growth in the solid-state switching industry. 2021 by the authors. Licensee MDPI, Basel, Switzerland.